2016 annual competitiveness analysis and growth slowdown analysis for ASEAN-10 - Tan, Khee Giap; Luu, Nguyen Trieu Duong; Nguyen, Le Phuong Anh (Asia Competitiveness Institute - World scientific series, 2017)
Based on a rich dataset of 121 indicators, the study covers four environments of competitiveness: (1) Macroeconomic Stability, (2) Government and Institutional Setting, (3) Financial, Businesses and Manpower Conditions, and (4) Quality of Life and Infrastructure Development. It then presents each economy's strengths and weaknesses, and conducts 'what-if' policy simulations to offer insights into the ASEAN economies. Through income-group specific econometric models, determinants of growth slowdown are identified and predictive probability of slowdown for each ASEAN economy is computed. Finally, progress of economic reforms in Cambodia, Laos, Myanmar and Vietnam is evaluated, from which policy implications for these countries' future development are drawn.